Implementation of the Swiss ordinance on maternity protection at work in companies in French-speaking Switzerland. - Abderhalden-Zellweger, Alessia; Probst, Isabelle; Politis Mercier, Maria-Pia; Zenoni, Michela; Wild, Pascal; Danuser, Brigitta; Krief, Peggy (Work, 2021)
BACKGROUND: Switzerland's Ordinance on Maternity Protection at Work (OProMa) requires that companies take the necessary measures to ensure that pregnant employees can continue working without danger. OBJECTIVE: To investigate the extent of compliance with OProMa within companies in French-speaking Switzerland as well as factors which facilitate and obstruct the ordinance's implementation. METHODS: A stratified random telephone survey of 202 companies from the healthcare and food industry was conducted. Descriptive and correlational statistics were calculated. Responses to open questions were analysed thematically. RESULTS: Only a minority of companies performed risk analyses or adapted employees' workstations, as per the legislation. OProMa was implemented more effectively in larger companies than smaller ones, in public rather than private ones, in the healthcare sector rather than the food industry, and when the person responsible for the wellbeing of pregnant employees within the company had undergone specific training on the subject. Data extrapolation suggested that only 2% of pregnant employees in French-speaking Switzerland's food industry and 12% in its healthcare sector are properly protected according to OProMa's provisions. CONCLUSIONS: Maternity protection in French-speaking Switzerland's companies urgently requires improvement. In addition to the apparent need for stronger incentives and for monitoring of companies, our findings indicate a need to provide them with resources to meet OProMa's provisions.